EXPLORING NARRATIVE VOICE IN EDWIDGE DANTICAT’S THE DEW BREAKER AND THE FARMING OF BONES - Sulaiman, Ibrahim T; Abdullahi , Bello S. (International Research Journal of Arts and Communication, 2024)
Most critical analyses of Edwidge Danticat’s works have primarily focused on context-based theories to explore the Caribbean people's historical, cultural, psychological, and political realities. However, there has been inadequate emphasis on her narratives' artistic and textual elements, particularly the examination of recurring narratological poetics. This paper aims to investigate the narratological poetics of narration (voice) in Edwidge Danticat’s The Dew Breaker (2004) and The Farming of Bones (1998) within the corpus of Caribbean literature. Using a qualitative approach, the research seeks to demonstrate the extent and purposes of deploying classical narratological poetics of narration (voice) in selected texts. The study argues that narratology offers unique insights into deciphering narrative structures and that narratological poetics/tenets are effective tools for studying narrative techniques. The research shows that the shift from homodiegetic to heterodiegetic narration and the shifting narratorial alliances from one character to another within a heterodiegetic narration allow The Dew Breaker, and by implication narrative texts, to represent different individual consciousnesses as they recreate their experiences. This is what lends The Dew Breaker its narratorial complexity, beauty, and aesthetic dexterity. The paper also reveals that narrative levels in The Farming of Bones add different perspectives and diversity to the narrative act of the text and increase the complexity and narrative aesthetics of the text. The research further demonstrates that intradiegetic narrations have both explicative and thematic functions in The Farming of Bones. The study argues that the classical narratological poetics of narration (voice) can determine the extent to which readers are guided or manipulated in relation to any given narrative text. Overall, Danticat’s narratives’ meanings and artistic complexities are influenced by the application of narration (voice) poetics, which serves to represent Haitian/Caribbean realities.